Current Insights on Early Life Nutrition and Prevention of Allergy - Ferrante, Giuliana; Carta, Maurizio; Montante, Claudio; Notarbartolo, Veronica; Corsello, Giovanni; Giuffrè, Mario (Frontiers in Pediatrics, 2020)
The incidence of allergic diseases in childhood appears to have significantly increased over the last decades. Since environmental factors, including diet, have been thought to play a significant role in the development of these diseases, there is great interest in identifying prevention strategies related to early nutritional interventions. Breastfeeding is critical for the immune development of newborns and infants through immune-modulating properties and it impacts the establishment of a healthy gut microbiota. However, the evidence for a protective role of breastfeeding against the development of food allergy in childhood is controversial, and there is little evidence to support the benefits of an antigen avoidance diet during lactation. Although it is not possible to draw a definitive conclusion about the protective role of breast milk against allergic diseases, exclusive breastfeeding is still recommended throughout the first 6 months of life due to associated health benefits. Furthermore, recommendations regarding complementary feeding in infancy have been significantly modified over the last few decades. Several studies have shown that delayed exposure to allergenic foods does not have a role in allergy prevention and recent guidelines recommend against delaying the introduction of complementary foods after 6 months of age, both in high- and low-risk infants. However, trials investigating this dietary approach have reported equivocal results so far. This review summarizes the available high-quality evidence regarding the efficacy of the principal dietary interventions proposed in early life to prevent allergic diseases in children.